PRODUCTIVITY OF TROPICAL LIMPET Cellana testudinaria ` (Linnaeus, 1758) LIVING ON THE ROCKY SHORE OF OHOIWAIT, SOUTHEAST MOLUCCAS, INDONESIA - Abraham . (JOURNAL OF COASTAL DEVELOPMENT, 2006)
Study on the productivity of tropical limpet C testudinaria has been carried out at approximatelv monthly intervals fom October 200] to September 2002. A total of 2404 limpets of 8.2 - 3],8 mm in size were obtained in ]2 month collections. The size structure of population presented 6 cohorts with accounting for 48% ofthe second cohort ofthe total population, The mean annual population biomass was estimated to be IOI3 1 748 mg AF DWm'2 or 2].8 kim`), hence the annual population production estimated by the mass specific growth rate method to be 2.8] gr.m`Z or 60. 7 K.Lm`2.yr